Economic Crisis and Electoral Participation in European Elections. An Assessment of the Relationship - Di Mauro, Danilo (PARTECIPAZIONE E CONFLITTO, 2016)
This article focuses on the relationship between the economy and electoral participation. Specifically, it aims to address the following question: what is the effect of the current economic crisis on European electoral turnout? According to the literature, economic reasons play an important role in both electoral participation and people’s party choices. The effects of a severe economic downturn, as the one ex-perienced in Europe during the last decade, are however only partially known. Does the economic crisis mobilize or weaken electoral participation? Does it have any impact at all? In order to assess the role of the economy, this work will employ the last three waves of the European Election Studies datasets and combine them with national economic indicators. Findings from competing multilevel models confirm a limited effect of the economic crisis at the personal, national and attitudinal level, particularly for the 2014 elections of the European Parliament.